Ring source potentials in two superposed fluids separeted by an inertial surface - B. N. Mandal; Krishna Kundu (International Journal of Mathematics and Mathematical Sciences)
The study of waves at the interface of two superposed fluids due to the presence of a vertical body of revolution requires the consideration of potentials due to horizontal ring sources submerged in one of the fluids. In this paper, the velocity potentials in the two fluids are computed due to a horizontal ring of sources of time-dependent strength submerged in either of the fluids of a two-fluid medium that are separated by an inertial surface.